Does neighbourhood deprivation affect the genetic influence on body mass?. (July 2017) - Owen, Gwilym; Jones, Kelvyn; Harris, Richard
Abstract: Most research into the role of gene-environment interactions in the etiology of obesity has taken environment to mean behaviours such as exercise and diet. While interesting, this is somewhat at odds with research into the social determinants of obesity, in which the focus has shifted away from individuals and behaviours to the types of wider obesogenic environments in which individuals live, which influence and produce these behaviours. This study combines these two strands of research by investigating how the genetic influence on body mass index (BMI), used as a proxy for obesity, changes across different neighbourhood environments measured by levels of deprivation. Genetics are incorporated using a classical twin design with data from Twins UK, a longitudinal study of UK twins running since 1992. A multilevel modelling approach is taken to decompose variation between individuals into genetic, shared environmental, and non-shared environmental components. Neighbourhood deprivation is found to be a statistically significant predictor of BMI after conditioning on individual characteristics, and a heritability of 0.75 is estimated for the entire sample. This heritability estimate is shown, however, to be higher in more deprived neighbourhoods and lower in less deprived ones, and this relationship is statistically significant. While this research cannot say anything directly about the mechanisms behind the relationship, it does highlight how the relative importance of genetic factors can vary across different social environments, and therefore the value of considering both genetic and social determinants of health simultaneously. Highlights: The study looks at interactions between genetics and neighbourhoods. Body mass index (BMI) is used as the dependent variable. A twin design and multilevel modelling procedure are employed. A greater genetic influence on BMI is found in deprived neighbourhoods. The importance of research into gene-environment interactions is highlighted.